Myeloid Leukemia Factor Acts in a Chaperone Complex to Regulate Transcription Factor Stability and Gene Expression. Issue 13 (30th June 2017) - Dyer, Jamie O.; Dutta, Arnob; Gogol, Madelaine; Weake, Vikki M.; Dialynas, George; Wu, Xilan; Seidel, Christopher; Zhang, Ying; Florens, Laurence; Washburn, Michael P.; Abmayr, Susan M.; Workman, Jerry L.
Abstract: Mutations that affect myelodysplasia/myeloid leukemia factor (MLF) proteins are associated with leukemia and several other cancers. However, with no strong homology to other proteins of known function, the role of MLF proteins in the cell has remained elusive. Here, we describe a proteomics approach that identifies MLF as a member of a nuclear chaperone complex containing a DnaJ protein, BCL2-associated anthanogene 2, and Hsc70. This complex associates with chromatin and regulates the expression of target genes. The MLF complex is bound to sites of nucleosome depletion and sites containing active chromatin marks (e.g., H3K4me3 and H3K4me1). Hence, MLF binding is enriched at promoters and enhancers. Additionally, the MLF-chaperone complex functions to regulate transcription factor stability, including the RUNX transcription factor involved in hematopoiesis. Although Hsc70 and other co-chaperones have been shown to play a role in nuclear translocation of a variety of proteins including transcription factors, our findings suggest that MLF and the associated co-chaperones play a direct role in modulating gene transcription. Graphical Abstract: Highlights: Myelodysplasia/myeloid leukemia factor (MLF) acts in a complex with DnaJ-1 and BCL2-associated anthanogene 2. The MLF-chaperone complex binds to chromatin and regulates transcription. The MLF-chaperone complex regulates the stability of transcription factors.